2022
DOI: 10.3389/frabi.2022.993271
|View full text |Cite
|
Sign up to set email alerts
|

Point prevalence survey to assess antibiotic prescribing pattern among hospitalized patients in a county referral hospital in Kenya

Abstract: Antibiotic resistance causes higher morbidity and mortality and higher healthcare costs. One of the factors influencing the emergence of antibiotic resistance is the inappropriate use of antibiotics. Clinical practitioners’ incorrect prescription patterns and a disregard for antibiotic usage recommendations are the leading causes of this resistance. This study examined the antibiotic prescription patterns among hospitalized patients at the Kiambu Level 5 hospital (KL5) to find potential for hospital quality im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Six articles were published from Ghana 43 48 . Four studies were reported from Kenya 49 52 . Equally two studies were reported from South Africa 33 , 53 and Tanzania 54 , 55 .…”
Section: Resultsmentioning
confidence: 99%
“…Six articles were published from Ghana 43 48 . Four studies were reported from Kenya 49 52 . Equally two studies were reported from South Africa 33 , 53 and Tanzania 54 , 55 .…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the prevalence of antibiotic use among hospitalized patients in Africa ranged from 27.6 to 83.5% [ 28 , 39 ]. The prevalence of antibiotic use was higher in West Africa (ranged from 51.4 to 83.5%) [ 19 , 21 , 22 , 25 27 , 29 , 33 , 35 37 , 39 41 , 47 , 48 ], followed by North Africa (79.1%) [ 20 ], East Africa (ranged from 27.6 to 73.7%) [ 28 , 30 32 , 34 , 38 , 42 44 ], and South Africa (ranged from 33.6 to 49.7%) [ 45 , 46 ]. The highest prevalence of antibiotic use was found in Nigeria (83.5%) [ 39 ], Ghana (82%) [ 25 ], Egypt (79.1%) [ 20 ], and Uganda (73.7%) [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of antibiotic use was higher among patients admitted to the ICU (64.4–100%; n = 9 studies) [ 30 , 32 , 36 , 38 , 40 , 42 44 , 47 ], followed by pediatric medical (10.6–94.6%; n = 13 studies) [ 21 , 22 , 30 , 32 , 35 , 36 , 38 , 40 , 42 44 , 47 , 48 ], neonatal (45.5–93.7%; n = 7 studies) [ 22 , 32 , 36 , 38 , 40 , 42 , 47 ], pediatric surgery (56.7–90.7%; n = 6 studies) [ 22 , 30 , 35 , 36 , 40 , 47 ], and adult surgical (22.9–82.9%, n = 12 studies) [ 21 , 22 , 30 , 32 , 35 , 36 , 38 , 40 , 42 44 , 47 ] ward. The rate of antibiotic use among patients hospitalized on other wards includes neonatal ICU (53.1–76.8%; n = 3 studies) [ 30 , 36 , 40 ], adult medical (19.5–73.6%; n = 13 studies) [ 21 , 22 , 30 , 32 , 35 , 36 , 38 , 40 , 42 44 , 47 , 48 ], and OBG/postnatal (6.7–92.5%; n = 8 studies) [ ...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations